Terrence Malick's Unseeing Cinema Memory, Time and Audibility - Batcho, James (Springer International Publishing, 2018)
This unique study opens up a new dimension of Terrence Malick's cinema - its expressions of unseeing and hearing. 'Unseeing' is Malick's means of transcending the moment in order to enter the life that unfolds; to treat cinema as a real experience for those who live its reality. In this way, Terrence Malick's Unseeing Cinema moves beyond film theory to advance a work of original philosophy, bringing together two thinkers not normally associated with one another: Gilles Deleuze and Søren Kierkegaard. It investigates how Malick's gatherings of time allow one to explore new philosophical questions about immanence and transcendence, ethics and faith, time and infinity, and the foldings of subjectivity that are central to both philosophers. Beyond cinema, it offers a way to think about our everyday repetitions and recollections and our ephemeral points of connection with those we love. .